Potential Drug–Drug Interactions in Medical Records of Patients With Atherosclerosis - Annora Rizky Amalia; Alfina Nurrahman; Wahyuddin Nur (Jurnal Infokes, 2026)
Background: Atherosclerosis is a cardiovascular disease that often requires combination pharmacotherapy, which may result in potential drug–drug interactions (pDDIs). Identifying pDDIs is important to support safe and effective medication use. This study aimed to evaluate potential drug–drug interactions based on the medical records of patients with atherosclerosis. Methods: This descriptive retrospective study used a purposive sampling technique. Medical records of patients with atherosclerosis who met the inclusion criteria were reviewed. Potential drug–drug interactions were identified using Medscape, Drugs.com, and verified with Stockley's Drug Interactions, 12th edition. Results: Among 71 patients, 14 (19.72%) had at least one potential drug–drug interaction. A total of 14 potential interaction pairs were identified, with the aspirin–ramipril combination being the most frequent, accounting for 8 of the 14 interaction pairs (57.14%). Conclusion: Potential drug–drug interactions were identified among hospitalized patients with atherosclerosis, with aspirin–ramipril being the most frequent interaction. Although the identified interactions were potential rather than clinically confirmed events, the findings highlight the importance of medication review and appropriate therapy monitoring to support patient safety.